DELEGATION OF AUTHORITIES AND DISTRIBUTION OF TASKS IN MANAGEMENT: ANALYSIS BASED ON FOREIGN EXPERIENCE AND UZBEKISTAN PRACTICE - Rakhmonberdi qizi, Aripova Dilbar (Journal of Higher Education and Academic Advancement, 2025)
Objective:  This article analyzes the theoretical and practical aspects of delegation of authority and task distribution within management systems. Method: Drawing on the experiences of the United Kingdom, Japan, and the United States, the study examines the effectiveness of delegation mechanisms and proposes recommendations for their implementation in the context of Uzbekistan. Results: Delegation is viewed as a key factor in enhancing management efficiency, strengthening trust between leaders and subordinates, and optimizing the use of human resources. Novelty: The paper provides methodological and practical value for leaders and administrators in the education sector.